The Impact of e-Learning Systems on Motivating Students and Enhancing Their Outcomes During COVID-19: A Mixed-Method Approach - Yahiaoui, Fethia; Aichouche, Riad; Chergui, Khalil; Brika, Said Khalfa Mokhtar; Almezher, Mohmmad; Musa, Adam Ahmed; Lamari, Imane Ahmed (Frontiers in Psychology, 2022)
E-learning is a key strategy in the course of higher education to improve the results of the educational process and stimulate student motivation. The Covid-19 pandemic imposed on Algerian universities to adopt the e-learning systems to search for effectiveness and efficiency of academic approaches. This paper seeks to remedy these problems by analyzing the impact of e-learning systems on student motivation and outcomes. A mixed-method approach was used in the data analysis; We conducted the study as a survey, with data being gathered via questionnaires distributed to 398 students. The questionnaire includes open questions that were qualitatively analyzed using content analysis with Nvivo, besides Likert scale questions were quantitatively analyzed and modelled using Structural equation modelling (SEM) with Amos to accomplish the path analysis of the research model. The results of the study showed that student motivation (Attention, Relevance, Confidence and Satisfaction) and student outcomes (knowledge, skills and attitudes) are significantly affected by e-learning systems (Technical and electronic requirements, personal requirements, perceived value and credibility of e-learning). The key findings are discussed, and they provide recommendations for future research